Protocol specification, testing, and verification, XII : proceedings of the IFIP TC6 WG 6.1, twelfth International Symposium on Protocol Specification, Testing, and Verification, Lake Buena Vista, Florida, U.S.A., 22-25 June, 1992 - Linn, R. J.; Uyar, M. U (IFIP transactions. Communication systems, 1992)
For more than a decade, researchers and engineers have been addressing the problem of the application of formal description techniques to protocol specification, implementation, testing and verification. This book identifies the many successes that have been achieved within the industrial framework and the difficulties encountered in applying theoretical methods to practical situations. Issues discussed include: testing and certification; verification; validation; environments and automated tools; formal specifications; protocol conversion; implementation; specification languages and models. C.